Does plastic incise drape prevent recolonization of endogenous skin flora during lumbar spine procedures? - Mohammadreza Zarei (International Journal of Preventive Medicine, 2019)
Background: The aim of this study was to compare the PID with bare skin (without PID) regarding bacterial recolonization and bacterial regrowth of the adjacent skin of surgical incision in lumbar spine surgery patients. Methods: This quasi-experimental study was conducted from February to May 2018 on 88 patients who were candidate for lumbar spine surgery. Patients were assigned to one of two groups, treatment (with PID) and control (without PID). Skin sampling (adjacent of surgical incision) for bacterial culture was done in two steps, immediately after surgical skin prep (IASSP) and immediately after surgical wound closure (IASWC) by researcher. Finally, samples were sent to the laboratory. Results: The mean total bacterial count of patient's skin in stage IASSP was not significantly different between treatment and control groups (0.34 vs 0.27, P = 0.68). However, mean total bacterial count in stage IASWC in treatment group was significantly higher than control group (2.2 vs 0.93, P = 0.03). The frequency distribution of S. aureus (P = 0.04) and S. epidermidis (P = 0.02) was significantly higher in treatment group compared with control group in stage IASWC. Conclusions: The results showed that using PID is unable to reduce recolonization and regrowth of bacteria on patients' skin adjacent to surgical wound in clean lumbar spine surgeries. However, making a definite decision about using or not using of PID requires further studies.